2022
DOI: 10.1186/s13195-022-01105-5
|View full text |Cite
|
Sign up to set email alerts
|

Combining tau-PET and fMRI meta-analyses for patient-centered prediction of cognitive decline in Alzheimer’s disease

Abstract: Background Tau-PET is a prognostic marker for cognitive decline in Alzheimer’s disease, and the heterogeneity of tau-PET patterns matches cognitive symptom heterogeneity. Thus, tau-PET may allow precision-medicine prediction of individual tau-related cognitive trajectories, which can be important for determining patient-specific cognitive endpoints in clinical trials. Here, we aimed to examine whether tau-PET in cognitive-domain-specific brain regions, identified via fMRI meta-analyses, allows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…When these imaging biomarkers were considered together in multimodal prediction models, one of the most parsimonious models included baseline tau and cortical thickness in the default mode network as the only predictors, suggesting complementary contributions of these measures to predicting clinical decline in atypical early AD. These findings are in line with previous investigations on biomarker-based prognostication in AD, which have provided converging evidence that tau PET is a superior predictor of cognitive decline compared with other measures of AD pathology and neurodegeneration including amyloid burden and gray matter atrophy in symptomatic AD patients [11][12][13][14][16][17][18][19][20] . This pattern of brain-behavior associations is also consistent with prior cross-sectional work by us and others.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…When these imaging biomarkers were considered together in multimodal prediction models, one of the most parsimonious models included baseline tau and cortical thickness in the default mode network as the only predictors, suggesting complementary contributions of these measures to predicting clinical decline in atypical early AD. These findings are in line with previous investigations on biomarker-based prognostication in AD, which have provided converging evidence that tau PET is a superior predictor of cognitive decline compared with other measures of AD pathology and neurodegeneration including amyloid burden and gray matter atrophy in symptomatic AD patients [11][12][13][14][16][17][18][19][20] . This pattern of brain-behavior associations is also consistent with prior cross-sectional work by us and others.…”
Section: Discussionsupporting
confidence: 90%
“…While the utility of tau PET for diagnosis is established (with FDA approval in 2020), evidence has recently begun accruing to demonstrate its clinical prognostic value in early symptomatic AD. In patients with typical MCI or mild dementia due to AD, those with relatively greater cerebral tau PET signal show a relatively faster decline in cognitive test performance on the Mini Mental State Examination [11][12][13][14][15][16][17] , Addenbrooke's Cognitive Examination 18 , or neuropsychological composite scores 11,14,15,19,20 . Given the importance of the Clinical Dementia Rating (CDR) scale as a clinical outcome measure in therapeutic trials and other studies (capturing both cognitive and functional impairment), surprisingly little work has been done on tau-based prognostication of longitudinal CDR change.…”
Section: Introductionmentioning
confidence: 99%
“…In Alzheimer disease (AD), amyloid-β (Aβ) is thought to initiate the spreading of neurofibrillary tau pathology from temporal-lobe epicenters to connected cortical regions, driving neurodegeneration and cognitive decline . Accordingly, Aβ-targeting therapies should ideally be applied at low tau levels to efficiently attenuate the AD cascade and slow tau-related neurodegeneration and clinical progression . It is therefore crucial to determine Aβ thresholds at which tau spreading is triggered to potentially inform treatment decisions …”
Section: Introductionmentioning
confidence: 99%
“…For a given value of p-tau217 concentration, we observed great variability in the global tau burden and regional pattern of tau-PET signal (Figure 1). Previous studies have shown that the regional patterns of tau-PET signal not only closely mirror current the clinical representation of AD related clinical syndromes 47 but also with future patterns of brain atrophy 23,24 as well as are correlated with domain-specific cognitive impairments [47][48][49] . This suggests that p-tau217 could serve as an important biomarker to assess the presence of tau pathology and disease severity, but tau-PET is advantageous for tracking regional specific tau pathology.…”
Section: Discussionmentioning
confidence: 90%